PENDAMPINGAN MASYARAKAT DALAM PELESTARIAN BUDAYA BANTENGAN DI KABUPATEN MOJOKERTO - RM BRAMASTYO KUSUMO NEGORO; Dwi Chandra Rizal A (Jurnal Pengabdian Dharma Wacana, 2020)
Bantengan in the Dutch colonial period in 1927 Claket, Mojokerto, East Java. The beginning of the formation of bantengan art begins with the establishment of martial arts whose originator named Mbah Siran. Before the existence of bantengan, Mbah Siran only trained pencak silat in the claket forest. Based on the discovery of a dead bull in the foot forest of Mount Welirang which was eventually dubbed the dead bull forest. From there it was also called Bantengan Art. Pencak silat in that year was actually not allowed by the invaders who were then colonized by the Dutch, did not abstain until there Mbah Siran and several students learned silat art silently in the forest at the foot of Mount Welirang which was to expel the invaders. When he found the dead bull, Siran got advice to take the bull's head and used it as a symbol of the bull which was also used to perform the bull's art, the bull's head was given the spirit of a dead bull to add to the attraction of bull art. The function of the banteng art in the following years is to enliven the organization such as weddings, circumcision, and other events. Bantengan art from mbah siran was named tri singly which means 3 musical instruments consisting of drums, saron, demung made into an art. However, because of this art, there is no written evidence at the present time due to damage eaten by insects and finally burned by the descendants of the second mbah siran named pak takiyat. which impact at this time is a struggle for many local and foreign parties including Malaysia.This is the cause of our burning enthusiasm to uphold the cultural values that exist in Mojokerto regency so that it can be preserved.